Identifying Opportunities for Advancing Weight Management in Primary Care - Ivana T. Croghan; Jon O. Ebbert; Jane W. Njeru; Tamim I. Rajjo; Brian A. Lynch; Ramona S. DeJesus; Michael D. Jensen; Karen M. Fischer; Sean Phelan; Tara K. Kaufman; Darrell R. Schroeder; Lila J. Finney Rutten; et al. (SAGE Publishing, 2019)
Objective: Much has been written about the patients' perspective concerning weight management in health care. The purpose of this survey study was to assess perspectives of primary care providers (PCPs) and nurses toward patient weight management and identify possible areas of growth. Patients and Methods: We emailed a weight management-focused survey to 674 eligible participants (437 [64.8%] nurses and 237 [35.2%] PCPs) located in 5 outpatient primary care clinics. The survey focused on opportunities, practices, knowledge, confidence, attitudes, and beliefs. A total of 219 surveys were returned (137 [62.6%] from nurses and 82 [34.4%] from PCPs). Results: Among 219 responders, 85.8% were female and 93.6% were white non-Hispanic. In this study, PCPs and nurses believed obesity to be a major health problem. While PCPs felt more equipped than nurses to address weight management ( P < .001) and reported receiving more training than nurses (50.0% vs 17.6%, respectively), both felt the need for more training on obesity (73.8% and 79.4%, respectively). Although, PCPs also spent more patient contact time providing weight management services versus nurses ( P < .001), the opportunity/practices score was lower for PCPs than nurses (−0.35 ± 0.44 vs −0.17 ± 0.41, P < .001) with PCPs more likely to say they lacked the time to discuss weight and they worried it would cause a poor patient-PCP relationship. The knowledge/confidence score also differed significantly between the groups, with nurses feeling less equipped to deal with weight management issues than PCPs (−0.42 ± 0.43 vs −0.03 ± 0.55, P < .001). Neither group seemed very confident, with those in the PCP group only answering with an average score of neutral. Conclusion: By asking nurses and PCP general questions about experiences, attitudes, knowledge, and opinions concerning weight management in clinical care, this survey has identified areas for growth in obesity management. Both PCPs and nurses would benefit from additional educational training on weight management.